2011
DOI: 10.1620/tjem.223.227
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Peripheral Blood Monocyte Fraction in Nonalcoholic Fatty Liver Disease

Abstract: An elevated white blood cell (WBC) count is associated with nonalcoholic fatty liver disease (NAFLD); however, a leukocyte subtype that is involved in the pathogenesis of NAFLD is not known. This study was conducted to investigate the association between NAFLD and WBC subtype fractions (%) among healthy elderly Koreans. A total of 794 subjects who underwent a health check-up were investigated. After excluding excessive alcohol intake and other liver diseases, NAFLD was diagnosed based on sonographic findings: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…TLC was found to be an independent predictor of the occurrence of NAFLD in the studied patients and the occurrence of fibrosis among NAFLD patients in the current study. This agrees with Kim HL et al . and Chung GE et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…TLC was found to be an independent predictor of the occurrence of NAFLD in the studied patients and the occurrence of fibrosis among NAFLD patients in the current study. This agrees with Kim HL et al . and Chung GE et al .…”
Section: Discussionsupporting
confidence: 93%
“…TLC was found to be an independent predictor of the occurrence of NAFLD in the studied patients and the occurrence of fibrosis among NAFLD patients in the current study. This agrees with Kim HL et al 19 and Chung GE et al 20 and could be explained by the state of systemic inflammation in NAFLD patients and endotoxin production from the fat stores. The accumulation of lipophilic persistent organic pollutants (POPs) in the adipose tissue leads to its slow release into the bloodstream.…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that the phenotypes, morphology, and transcriptome of the splenic monocytes resemble those of blood monocytes . Importantly, Kim et al reported that circulating monocytes were increased in patients with NAFLD compared with normal subjects, suggesting an association between the number of circulating monocytes and hepatic inflammation. Our data here showed a positive correlation between the percentages of monocytes in the spleen and hepatic mRNA abundance of Ccl2 , a chemokine that mediates monocyte recruitment .…”
Section: Discussionmentioning
confidence: 99%
“…However, although gender was accounted for during the analysis, the results of that study were not stratified according to gender and the criteria used to determine quartiles of patients based on WBC count were not gender-specific. In contrast, we analysed the data according to gender as WBC counts differ significantly between men and women [18, 19]. …”
Section: Discussionmentioning
confidence: 99%